What is advertising without blending? Advertisments in women’s magazines - Nihada Delibegović Džanić; Alma Žerić (ExELL (Explorations in English Language and Linguistics))
Conceptual integration theory, proposed by Fauconnier and Turner in 1993, has been successfully used in the study of a wide range of phenomena of human thought and action, from counterfactuals to met-aphors, proving blending to be present in the simplest kinds of human thinking. In that sense, conceptual integration theory has emerged as a powerful theory that can account for a wide variety of linguistic and non-linguistic phenomena. Therefore, it is not surprising that conceptual integration theory has found its application in the study of advertising. Advertising requires both conscious and subconscious mental interpretation of the hidden messages. The primary objective of this paper is to show that conceptual integration theory is equipped with the mechanisms that can explain the construction of the meaning of text-image advertisements. Specifically, analyzing several text-image advertisements in women’s magazines, this paper attempts to explore to what extent hidden cognitive mechanisms involved in the interpretation of advertising can be explained using the postulates of conceptual integration theory.